ANALISIS SOCIAL MEDIA MARKETING COFFEE SHOP KOMPOSISI MENGGUNAKAN THE CIRCULAR MODEL OF SOME (STUDI PADA INSTAGRAM @KOMPOSISI_ID) - Livvya Laksmitha Cahyaningtyas; Pratami Wulan Tresna; Cecep Safa'atul Barkah (JURNAL LENTERA BISNIS, 2024)
Social media marketing is a strategy that is often used by businesses such as the coffee shop Komposisi on Instagram @komposisi_id. The results of the existing engagement rate have not reached the target, so an analysis was carried out to find out the cause in depth using the model from The Circular Model Of SOME. This study uses a qualitative method by reducing data, presenting data, and determining conclusions, as well as data collection techniques through interviews with five informants, observing Instagram @komposisi_id, and literature studies. As a result, the social media marketing of the coffee shop Komposisi on Instagram has been implemented properly based on the implementation of the share and optimize stages. However, the implementation of the manage and engage stages has not been effective because it has not been implemented properly, indicating the need for improvements and improvements to the overall stages to further increase engagement.